Non-response to first-line hormonal treatment for symptomatic endometriosis: overcoming tunnel vision. A narrative review - Giulia Emily Cetera; Camilla Erminia Maria Merli; Federica Facchin; Paola Viganò; Elisa Pesce; Francesca Caprara; Paolo Vercellini (BMC, 2023)
Abstract One-fourth to one-third of women with endometriosis receiving first-line hormonal treatment lacks an adequate response in terms of resolution of painful symptoms. This phenomenon has been ascribed to "progesterone resistance", an entity that was theorized to explain the gap between the ubiquity of retrograde menstruation and the 10% prevalence of endometriosis among women of reproductive age. Nevertheless, the hypothesis of progesterone resistance is not free of controversies. As our understanding of endometriosis is increasing, authors are starting to set aside the traditionally accepted tunnel vision of endometriosis as a strictly pelvic disease, opening to a more comprehensive perspective of the condition. The question is: are patients not responding to first-line treatment because they have an altered signaling pathway for such treatment, or have we been overlooking a series of other pain contributors which may not be resolved by hormonal therapy? Finding an answer to this question is evermore impelling, for two reasons mainly. Firstly, because not recognizing the presence of further pain contributors adds a delay in treatment to the already existing delay in diagnosis of endometriosis. This may lead to chronicity of the untreated pain contributors as well as causing adverse consequences on quality of life and psychological health. Secondly, misinterpreting the consequences of untreated pain contributors as a non-response to standard first-line treatment may imply the adoption of second-line medical therapies or of surgery, which may entail non-negligible side effects and may not be free of physical, psychological and socioeconomic repercussions. The current narrative review aims at providing an overview of all the possible pain contributors in endometriosis, ranging from those strictly organic to those with a greater neuro-psychological component. Including these aspects in a broader psychobiological approach may provide useful suggestions for treating those patients who report persistent pain symptoms despite receiving first-line hormonal medical treatment.